2020
DOI: 10.3390/toxins12010052
|View full text |Cite
|
Sign up to set email alerts
|

Patulin Mycotoxin in Mango and Orange Fruits, Juices, Pulps, and Jams Marketed in Pakistan

Abstract: The objective of the study was to explore the incidence of patulin (PAT) mycotoxin in mango and orange fruits and derived products marketed in Pakistan. A total of 274 samples, including 70 mango fruits, 63 mango-based products (juices, pulp, and jam), 77 orange fruits, and 64 orange-based products, were collected. PAT was determined by reverse-phase high-performance liquid chromatography (HPLC) with UV-Vis detector (276 nm). Linear detector response was observed (R2 > 0.99), the limit of detection (LOD) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
0
30
1
Order By: Relevance
“…The PAT levels in citrus fruits from Pakistani Punjab and northern Pakistan were significantly different by applying ANOVA (p < 0.05). The present survey results show that PAT contamination in citrus fruits is much higher than that previously reported for mango and orange fruits [27]. In that case, 74 out of 141 samples of orange fruits, juices, pulp, and orange jams were found to contain PAT, and only in one sample did the level exceed 50 µg/kg.…”
Section: Occurrence Of Pat In the Citrus Fruit Samplescontrasting
confidence: 60%
See 2 more Smart Citations
“…The PAT levels in citrus fruits from Pakistani Punjab and northern Pakistan were significantly different by applying ANOVA (p < 0.05). The present survey results show that PAT contamination in citrus fruits is much higher than that previously reported for mango and orange fruits [27]. In that case, 74 out of 141 samples of orange fruits, juices, pulp, and orange jams were found to contain PAT, and only in one sample did the level exceed 50 µg/kg.…”
Section: Occurrence Of Pat In the Citrus Fruit Samplescontrasting
confidence: 60%
“…PAT results in different cultivars of citrus fruits are more comprehensive interims of samples analyzed and from central and northern areas were covered during analysis. However, only two reports [ 22 , 27 ] are documented demonstrating the presence of PAT in fruits and juices. In our previous research [ 22 ], however, citrus fruits were never included and assessed for PAT presence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ochratoxin A (OTA), the major mycotoxin of the ochratoxins, is produced by various species of the Aspergillus and Penicillium genus [ 8 ]. In addition, Penicillium species are known to produce mycophenolic acid (MPA) [ 9 ] and patulin (PAT) [ 10 , 11 ]. Aflatoxins, including aflatoxin B1 (AFB1), aflatoxin B2 (AFB2), aflatoxin M1 (AFM1), aflatoxin M2 (AFM2), aflatoxin G1 (AFG1), and aflatoxin G2 (AFG2), are the most studied group of mycotoxins produced by Aspergillus flavus [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…El Jai et al [1] used liquid chromatography coupled to time-offlight mass spectrometry to analyse mycotoxins and conjugated mycotoxins; there were a total of 14 mycotoxins in 40 samples of aromatic medicinal plants (AMPs) from Morocco. Hussain et al [2] analyzed patulin in 274 fruit and derived products samples from Pakistan, and Silva et al [3] evaluated the presence of ochratoxin A in 85 beer samples from Portugal. These results revealed that regular monitoring of cereals or fruits and their products (beer, juices, pulps and jams) during the harvest and processing stages is recommended to enhance the confidence in final consumers.…”
mentioning
confidence: 99%